Design and fabrication of indigenous multi-rotational thorax phantom for patient-specific quality assurance of IMRT and VMAT. Issue 5 (3rd June 2022) - Kesavan, G.; Senthilkumar, S.; Hariprasanth, K.
Abstract : Intensity-modulated radiotherapy (IMRT) and volumetric-modulated arc therapy (VMAT) are commonly used treatment modalities in external beam radiotherapy. Precise quality assurance is required for the clinical implementation of IMRT and VMAT to ensure the correct treatment delivery. Square slab phantom is used commonly in developing countries to measure the pre-treatment point dose measurements. The limitation of the slab phantom was that the detector was positioned on the central axis of the beam which caused difficulty in positioning of the chamber at off-axis of the beam and peripheral regions. The new indigenously multi-purpose multi-rotational phantom was fabricated with various chamber provisions in order to address the above challenge. Innovative devices always play a crucial role in radiotherapy to bring significant technological advancement to the field. The quality assurance Multi-Rotational Thorax (MRT) Phantom designing involved slice-wise modelling of an average adult thorax using Poly-methyl methacrylate (PMMA) to perform point dose absolute dosimetry using an ionization chamber and Radio-Photo-Luminescence Glass Dosimeter (RPLGD). The phantom consisted of 35 slices of PMMA material in an axial direction. Each slice had a dimension of 1 cm thickness, 35 cm length and 20 cm height. The phantom had provisions in the target region and multiple provisions in the lungs, heart, surface and spine. The unique manual rotation system was provided on the lungs as well as in the heart. The provisions were capable of holding the detectors such as ionization chambers and RPLGD. The response of the phantom to open the beam in various gantry angles was initially accessed with multiple gantry angles and then pre-treatment verification of IMRT and VMAT plans was also checked. The results showed that the MRT phantom had good capabilities for absolute point dosimetry. In the case of an open beam, multiple gantry angles, the maximum variations for both the detectors were within −1.9% when compared with the TPS dose. The maximum percentage variation on isocentre (T) for IMRT and VMAT between TPS and Semiflex chamber was 1.85%. Similarly, the maximum percentage variation was 1.92% between TPS and RPLGD on isocentre. For Semiflex chamber, maximum percentage variation on peripheral region was 2.68%. Similarly, for RPLGD maximum percentage variation was 2.76%. The overall difference between the measured values for both the detectors were less than 3%. The present dosimetric study concluded that the MRT phantom with a RPLGD and Semiflex chamber was suitable for routine IMRT and VMAT patient-specific QA purposes.